Blocking Tumor-Educated MSC Paracrine Activity Halts Osteosarcoma Progression - Baglio, S Rubina; Lagerweij, Tonny; Pérez-Lanzón, Maria; Ho, Xuan Dung; Léveillé, Nicolas; Melo, Sonia A; Cleton-Jansen, Anne-Marie; Jordanova, Ekaterina S; Roncuzzi, Laura; Greco, Michelina; van Eijndhoven, Monique A J; Grisendi, Giulia; et al. (Clinical cancer research, 2017)
Human osteosarcoma is a genetically heterogeneous bone malignancy with poor prognosis despite the employment of aggressive chemotherapy regimens. Because druggable driver mutations have not been established, dissecting the interactions between osteosarcoma cells and supporting stroma may provide insights into novel therapeutic targets. By using a bioluminescent orthotopic xenograft mouse model of osteosarcoma, we evaluated the effect of tumor extracellular vesicle (EV)-educated mesenchymal stem cells (TEMSC) on osteosarcoma progression. Characterization and functional studies were designed to assess the mechanisms underlying MSC education. Independent series of tissue specimens were analyzed to corroborate the preclinical findings, and the composition of patient serum EVs was analyzed after isolation with size-exclusion chromatography. We show that EVs secreted by highly malignant osteosarcoma cells selectively incorporate a membrane-associated form of TGFβ, which induces proinflammatory IL6 production by MSCs. TEMSCs promote tumor growth, accompanied with intratumor STAT3 activation and lung metastasis formation, which was not observed with control MSCs. Importantly, intravenous administration of the anti-IL6 receptor antibody tocilizumab abrogated the tumor-promoting effects of TEMSCs. RNA-seq analysis of human osteosarcoma tissues revealed a distinct TGFβ-induced prometastatic gene signature. Tissue microarray immunostaining indicated active STAT3 signaling in human osteosarcoma, consistent with the observations in TEMSC-treated mice. Finally, we isolated pure populations of EVs from serum and demonstrated that circulating levels of EV-associated TGFβ are increased in osteosarcoma patients. Collectively, our findings suggest that TEMSCs promote osteosarcoma progression and provide the basis for testing IL6- and TGFβ-blocking agents as new therapeutic options for osteosarcoma patients. .